The quality of education in opinion of nursing and physiotherapy students accomplished in Erasmus Programme in the Finish Mikkeli University of Applied Sciences – preliminary study - Cuber, Tomasz; Woronowicz, Urszula (Nursing in the 21st Century, 2025)
Introduction. The term of quality is multidimensional and ambiguous. Its dynamics is very often emphasised. The meaning that is attributed to this term also depends on the circumstances in which people refer. Nowadays the market of educational services is very broad, so the quality of education at higher schools should play the main role in university management. The crucial element in assessment of the quality of education is monitoring of students’ opinion about educational offer. Erasmus Programme (the European Community Action Scheme for the Mobility of University Students) enables students to go abroad and partly study there, promotes the mobility of academic teachers and scientists to participate in international study projects. The aim of the study. The aim of the study was to assess the level of quality of educational offer among students who participated in Erasmus Programme offered by the Finish Mikkeli University of Applied Sciences. Material and Methods. The study that concerns the students’ opinion about the quality of educational offer of Erasmus Programme was carried out by the use of case study method among the group of students from four countries: USA, Portugal, Greece and Poland. All of them participated in international education for nursing and physiotherapy students offered by the Mikkeli University of Applied Sciences between 1st of September and 30th of November 2008. Results. On the basis of the conducted study that aimed the assessment of the quality of education among students who participated in Erasmus Programme the main outcome was that they evaluated it on a high level. The higher rank was ascribed to the quality of offered information and academic teachers’ competence. Negative opinion was given to the quality of information about Erasmus Programme itself and too little possibility of mobility in choosing institutions where students could have been professionally trained and too short period of education.